Acute renal and neurotoxicity due to weight-based dosing of intravenous acyclovir: How to dose in obese patients?. (October 2020) - Sallevelt, Bastiaan TGM; Smeijsters, Erin H; Egberts, Toine CG; van der Elst, Kim CM; Mudrikova, Tania
Highlights: Clinical guidelines on the dosing of acyclovir in obese patients are inconsistent. We recommend to dose high-dose intravenous acyclovir based on adjusted body weight (AdjBW) in obese patients. We recommend early and intense monitoring of neurological symptoms, urinary output and renal function. Acyclovir neurotoxicity can mimic the signs and symptoms of neurological viral infections. Early-stage therapeutic drug monitoring can be used for dose guiding in obese patients. Abstract: Background: Acyclovir is a hydrophilic drug that is mainly distributed in the lean compartments of the body. Consequently, dosing on total body weight in obese patients may lead to drug overdosing. Inconsistency in clinical guideline recommendations and a lack of clear recommendations in the Summary of Product Characteristics on how to dose acyclovir in obese patients can impede safe and effective treatment. Case report: This report describes a 71-year-old obese patient (body mass index 35 kg/m 2 ) with herpes zoster ophthalmicus and meningoencephalitis. The patient had normal renal function and was treated with acyclovir with a dosage based on actual body weight (10 mg/kg q8h intravenously). Supratherapeutic acyclovir concentrations probably induced acute kidney injury (AKI) and neurotoxicity. Results: Due to the severity of the toxic effects, multiple sessions of hemodialysis were necessary, with eventual full recovery of the renal function and neurotoxic symptoms. Low dose haloperidol and lorazepam were not effective in resolving audiovisual hallucinations in our patient. Conclusion: This case report emphasizes the need for adjusted dosing and subsequent close monitoring of obese patients who are treated with hydrophilic drugs, such as acyclovir, to avoid patient harm. We discuss prevention and management strategies for acyclovir toxicity in obese patients based on the current literature.